PHARMACOGNOSTIC, PHYSICOCHEMICAL, AND PHYTOCHEMICAL STUDIES ON STEM BARK OF ZANTHOXYLUM ARMATUM DC. - G, JOTHI; K, KEERTHANA; G, SRIDHARAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: To analyze the microscopic, macroscopic, physicochemical, and phytochemical standards of the Zanthoxylum armatum DC. (stem bark). Methods: Pharamacognostic studies, namely macroscopic, microscopic, and powder microscopic analysis of stem bark were carried out. Physicochemical standards - ash content including total ash content, water soluble, and acid insoluble ash values, moisture content by loss on drying, solubility and extractive values of Z. armatum DC. were determined. Preliminary phytochemical screening, fluorescence analysis and quantification of alkaloids, flavonoids, phenol, tannins, saponins, and terpenoids were also studied. Results: The macroscopic studies of stem bark showed the stem and its branches, armed with long, sharp prickles with variable size. The transverse section of bark showed the phellogen, phelloderm, cortex, phloem, and medullary rays that are characteristics to Z. armatum DC. The results of physicochemical standards give the identity and purity of the selected sample. Phytochemical studies revealed the presence of alkaloids, flavonoids, phenols, tannins, saponins, and terpenoids. Conclusion: The present findings provide the pharmacognostic, physicochemical, and phytochemical information about the stem bark of Z. armatum and this might be useful by providing additional support with regard to its identification and standardization parameters.